Literature review on the usage of six sigma techniques for improvement of quality in soft drink beverage and bottling industries. Issue 1 (January 2021) - SM, Khwaja Mohinuddin; Vivekanand, V; Jayakumar, C
Abstract: The main goals of a manufacturing plant is to improve quality, throughput and increase productivity by reducing ineffective time. In order to do so various areas needs to be looked at and one such focus is on quality improvement, quality has various dimension's and meeting all these dimension require a sound approach like Six Sigma. The soft drink beverage industry has a complex manufacturing process and there are strict quality measures due to the direct relation which it has with its consumers. In order to accomplish such a need six sigma approach is essential. In regard to the beverage industry quality issues starts of from carbon dioxide yield to bottle filling issues. This study focusses on bringing in different literature which have used six sigma tools and techniques in the bottle and beverage industry. Based on the study it was found techniques such as pareto analysis, fish bone diagram, design of experiment, analysis of variance (ANOVA), control charts are widely used. This is done in order to provide a sound framework on what techniques can be applied when an issue on quality arises.